Cultures of economic education: Grammar school curricula in a multilingual comparison - Ruoss, Thomas; Ackermann, Nicole; Stadelmann, Talia (European Educational Research Journal, 2023)
Reinforcement of differences in educational systems and school curricula may be expected in Europe due to societal crises and transformations. Thus, it is likely that cultural “variants of a capitalist spirit” and different concepts of economic education will become evident in a corresponding curriculum analysis. In this study, we focused on cultures of economic education at the level of grammar school curricula in a federal, multilingual context. We aimed to compare subject content in curricula and identify structural characteristics (e.g. regional language, graduation rates, and cantonal university) associated with differences in subject content. Taking Switzerland as an example, we compiled a representative dataset with 47 curricula and qualitatively analyzed subject content. The results showed that subject content clearly differs in terms of curriculum language, but no clear pattern was found regarding other structural characteristics. We concluded that cultural “variants of a capitalist spirit” are present differently across language regions. This perspective on local differences may help us to understand conflicting goals and measures when facing economic crises on a global level.